KADAVRALARDA N.İSCHİADİCUS'UN SEYRİ VE DALLANMALARI ÜZERİNDE MAKROANATOMİK ÇALIŞMALAR - ÇETİN, AYMELEK (Fırat Üniveristesi, 1990)
Bu araştırma kadavralarda n.ischiadicus'un hangi liflerin birleşmesiyle oluştuğunu belirlemek ve motor-kuten dallarını incelemek amacıyla yapıldı. Pelvis bölgesi açıldı. Vertebra corpuslarına ulaşıldı. N. ischiadicus'un L4'ten gelen ince bir lif ile L5-S1-2'den gelen liflerin birleşmesiyle oluştuğu gözlendi. Foramen infrapiriforme'den geçerek uyluk arkasına geldiği gözlendi. Uylukta fossa poplitea'ya gelmeden n.tibialis ve n.peroneus communis dallarına ayrılmaktaydı. N.tibialis bacağa geçişi sırasında genellikle (%83) n.suralis'i tek başına vermekteydi. N.peroneus communis, collum fibula çevresinden geçerek bacağın ön yüzüne gelmekteydi. Bu sırada kuten dal vermemektedir. M.peroneus longus'un başlangıç lifleri arasında n. peroneus profundus ve n. peroneus superficialis dallarına ayrılmaktaydı. N peroneus profundus, bacağın ön grup kaslarına motor dal vermektedir. N. peroneus superficialis, peroneal kaslara motor lif vermektedir. Bacağın distalinde n. peroneus superficialis iki dala ayrılmaktadır. İç taraftaki dal ayak başparmağının medial kısmına ve 2.-3.parmaklar arasındaki bölgeye kuten dal vermektedir. Dış taraftaki dal 3.-4.parmaklar arasındaki bölgeye kuten dal vererek sonlanmaktadır.

The aim of this research is to identify the fibers that form the sciatic nerve and examine the motor-sensory branches of the nerve on cadavers. Pelvic region was opened up to reach vertebral corpuses. It was observed that a thin fiber from L4 and fibers from L5-S1-2 form the sciatic nerve. It was also seen that the nerve reached the back of the femur by passing through foramen infrapiriforme. The sciatic nerve divided into two branches: tibial nerve and common peroneal nerve before reaching popliteal fossa. The tibial nerve was generally found to give off the sural nerve alone while reaching the leg (83%). Common peroneal nerve reached the front of the leg by passing around collum fibula and gave off a sensory branch at the same time. Between the original fibers of m. peroneus longus, it divided branches of n. peroneus profundus and n. peroneus superficialis. N. peroneus profundus gave off a motor branch to anterior muscles of the leg. N. peroneus superficialis gave off a motor fiber to peroneal muscles. In the distal part of the leg, n. peroneus superficialis divided into two branches. The internal branch gave off a sensory branch to the medial side of the big toe and the area between second and third toes, while the external branch ended by giving off a sensory branch to the area between third and fourth toes
Macroanatomic studies on branching and running of the sciatic nerve on cadavers
Keywords: Anatomi; Anatomy